Stability and Sensitivity Analysis of Digital Filters under Finite Word Length Effects via Normal Form Transformation - Murty, K.N.; Reddy, K.V. (Электронное моделирование, 2012)
Main objective of this paper is to present the general solution of the first order matrix difference system X (n+1)=AX (n)B+C(n)U(n)D(n), and then study the stability and sensitivity analysis of the digital filters via eigenvalue sensitivity and normal form transformations. Предложено общее решение разностной системы матриц первого порядка X (n+1)=AX (n)B+C(n)U(n)D(n). Исследована стабильность и чувствительность цифровых фильтров посредством анализа чувствительности собственного значения и преобразования нормальной формы. Запропоновано загальний розв’язок різницевої системи матриць першого порядку X (n+1)=AX (n)B+C(n)U(n)D(n). Досліджено стабільність і чутливість цифрових фільтрів за допомогою аналізу чутливості власного значення та перетворення нормальної форми.